2000
DOI: 10.2106/00004623-200002000-00045
|View full text |Cite
|
Sign up to set email alerts
|

Step Activity Monitor: Increased Accuracy in Quantifying Ambulatory Activity

Abstract: Summary: This study compares the accuracy of a two-dimensional accelerometer worn on the ankle (a step activity monitor) with that of an electronic, digital pedometer worn on the belt line. Twcnty-nine human subjects were evaluated while they briskly walked 400 M, slowly walked 10 M. and ascended and dcsccndcd a flight 01 stairs. The step activity monitor had less error in all activities; its mean absolute error was 0.54%, whereas that of the pedometer was 2.82%. The difference was more pronounced in obese sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 0 publications
3
41
0
Order By: Relevance
“…Future versions of the IDEEA 1 system will be able to address this topic. The average number of steps taken per day by the patients in our study (6078 ± 3806) represents a 22% increase over averages reported previously (4988 steps per day in 111 patients) [36,52,53,63]. Although this increase is substantial, it does fall within the wide range of activity (395-17,718 steps per day) that has been described in the same studies.…”
Section: Discussionsupporting
confidence: 61%
“…Future versions of the IDEEA 1 system will be able to address this topic. The average number of steps taken per day by the patients in our study (6078 ± 3806) represents a 22% increase over averages reported previously (4988 steps per day in 111 patients) [36,52,53,63]. Although this increase is substantial, it does fall within the wide range of activity (395-17,718 steps per day) that has been described in the same studies.…”
Section: Discussionsupporting
confidence: 61%
“…Step activity monitors (SAMs) (Prosthetics Research Study, Seattle, WA, USA) were used to record the performance of daily walking activity [19]. The SAM is a reliable and valid tool for the measurement and recording of walking activity [20].…”
Section: Instrumentation and Proceduresmentioning
confidence: 99%
“…[21] However, the major limitations of many pedometers are their accuracy and reliability [21,22] because they are worn at the waist and thus are sensitive to vertical movement. Therefore, the response may be affected by position, mode of the pedometer attachment, movement style, and walking speed of the individual being monitored.…”
Section: Introductionmentioning
confidence: 99%
“…Self-report measures of walking activity have been reported to be imprecise compared with objective measures. [19,20] Relatively new techniques allowing unobtrusive long-term activity monitoring with the use of pedometers and microprocessor-based accelerometer recorders may provide a clearer view of how much an individual actually walks in his/her own surroundings.[21] However, the major limitations of many pedometers are their accuracy and reliability [21,22] because they are worn at the waist and thus are sensitive to vertical movement. Therefore, the response may be affected by position, mode of the pedometer attachment, movement style, and walking speed of the individual being monitored.…”
mentioning
confidence: 99%
See 1 more Smart Citation